2015
DOI: 10.1161/circresaha.116.302706
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mineralocorticoid Receptor Antagonists in Cardiovascular Disease

Abstract: Aldosterone exerts its best known sodium homeostasis actions by controlling sodium excretion at the level of the distal tubules via activation of the apical epithelial sodium channel (ENaC) and the basolateral Na+/K+ ATPase pump. Recently, this mineralocorticoid hormone has been demonstrated to act on the heart and blood vessels. Excess release of aldosterone in relation to the salt status induces both genomic and non-genomic effects that by promoting endothelial dysfunction, and vascular and cardio-renal adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 115 publications
(111 reference statements)
0
50
0
4
Order By: Relevance
“…7,21 Its antagonists (spironolactone and eplerenone) are part of the standard therapeutic regimen for treating heart failure in clinical practice. 22 Although animal studies have shown promising data that these antagonists may be beneficial for restenosis after PCI, they have not been clinically proved.…”
Section: Discussionmentioning
confidence: 99%
“…7,21 Its antagonists (spironolactone and eplerenone) are part of the standard therapeutic regimen for treating heart failure in clinical practice. 22 Although animal studies have shown promising data that these antagonists may be beneficial for restenosis after PCI, they have not been clinically proved.…”
Section: Discussionmentioning
confidence: 99%
“…[236][237][238][239][240][241][242][243][244][245][246][247] Aldosterone blockade by spironolactone was shown to reduce all-cause mortality in adults with symptomatic HF by 35% when it was added to standard HF therapy in the RALES trial (Randomized Aldactone Evaluation Study). 248 Subsequently, eplerenone was found to provide a similar survival benefit in adults with HF caused by LV dysfunction 249,250 In addition to improving survival and hospitalization rates, canrenone and spironolactone have been associated with reverse remodeling in adults with HF.…”
Section: Mineralocorticoid Antagonistsmentioning
confidence: 99%
“…Alternative important mechanisms that are involved in the development of aldosterone-induced morbidity and mortality include inflammation, apoptosis, cell proliferation, matrix formation, collagen deposition, fibrosis, ROS generation, cell adhesion, baroreflex dysfunction, vasoconstriction, endothelial dysfunction, platelet activation and pro-arrhythmogenicity Ferrario and Schiffrin, 2015;Fuller and Young, 2005;Funder, 2009;Kontak et al, 2010;McCurley and Jaffe, 2012;Nguyen Dinh Cat and Jaisser, 2012;Rocha and Funder, 2002;van den Berg et al, 2014). These effects may all contribute to the aldosterone-associated premature pro-atherogenic and prothrombotic effects, being the pathogenic explanation for the increased risk of cardiovascular morbidity and mortality in patients with PA.…”
Section: Consequences Of Aldosterone Excessmentioning
confidence: 99%
“…Preclinical and clinical studies have shown that pathological effects of exposure to excess aldosterone can be attenuated and even prevented by antagonizing the aldosterone effects on the MR (Bauersachs et al, 2015;Ferrario and Schiffrin, 2015). In animal studies, spironolactone has well proven beneficial effects on many pathogenetic mechanism that are involved in the development of cardiovascular complications and these effects are independent from its hypotensive effect per se.…”
Section: Spironolactonementioning
confidence: 99%